Análise das políticas curriculares da rede pública municipal de educação de Foz do Iguaçu à luz da pedagogia histórico-crítica (2007-2017) - Marquezi, Jussara (2019)
Creating this study at the dawn of historic-critical pedagogy means comprehending a historical movement which aims for the integral education of people, with the purpose of positively interfering on society and contribute to its transformation, as historical materialism theory proposes, presented in the Associação dos Municípios do Oeste do Paraná (AMOP) curriculum, which is in place at the city of Foz do Iguaçu since 2007. However, on the national spectrum, this curriculum has become an idealistic education concept after the implementation of the Laws and Guidelines for National Education (LDBEN 9394/96) and new norms were made for all education nationwide. Having this theorical dispute as a background, given their antagonistic conceptions, elucidate on which of those two is being used as an educational guideline on a municipal level has become a major focal point. With this in mind, this work’s main objective was to verify if historic-critical pedagogy is indeed present on curriculum policies, as well as in the curriculum in place at the municipal level in Foz do Iguaçu from 2007-2017. With that purpose, on a dialectic approach to data analysis, this work’s journey consisted, initially, with a brief historical contextualization of the public school system of Paraná’s westernmost region, focusing mainly on the development of the educational system in the city of Foz do Iguaçu, since it’s colonization up to the present day, as a means to reflect on the social contradictions that presented themselves during this period. To substantiate this research, a theoretical study made itself needed, on which we evaluated historic-critical pedagogy’s methodology, as well it’s theoretical fundaments, so we could further analyze Foz do Iguaçu’s public school system curriculum guidelines, such as the AMOP Curriculum, the pedagogue-politic guideline and the Continued Education Report from the Municipal Technology Nucleus, with the intention of finding the main focal points of the pedagogy system implemented on the city. To further complement this discussion, structured interviews created jointly with AMOP’s pedagogy executive office as well as municipal secretaries of education that operated during this period, were made. This approach produced investigative data which helped correlate information gathered from personnel with those from official documents and theoretical analysis. Through the analysis displayed on this research, we hope to demonstrate that historic-critical pedagogy is indeed implemented, however, due to the influence of opposing pedagogical fields, the curricular guidelines present on the public school system of Foz do Iguaçu during this period are constrained by neo-liberal policies, hindering their effectiveness.